Rekonstruksi Pengelolaan Zakat atas Hasil Tambang (Ma’din) dan Barang Temuan (Rikaz) dalam Perspektif Fiqih Kontemporer - Risa Umami; Inayatul Qudsiyah (Cashless : Journal of Sharia Finance and Banking, 2025)
Zakat is a religious fiscal instrument that plays a strategic role in wealth redistribution and poverty alleviation. Among the objects of zakat with massive economic potential yet often overlooked are mining products (ma'din) and found objects (rikaz). This article aims to analyze in-depth the sharia provisions related to zakat on mining and rikaz through a descriptive qualitative approach. The study results indicate that differences in acquisition characteristics result in different zakat levels, namely 2.5% for mining and 20% for rikaz. Professional management in this sector is expected to become a pillar supporting the economic independence of the community.